Exploring the neighbourhood context of serious assaults on police - Gibbs, Jennifer C. (Policing and society, 2018)
While evidence of social structural factors influencing violence against police (VAP) exists, few studies spatially explore this phenomenon with geographical aggregations smaller than the city level. The purpose of this study is to contribute to filling this gap in the literature. Using the census tract as the unit of analysis, the number of incidents per tract where Baltimore police officers were injured or assaulted with firearms in the line of duty was compared with theoretical indicators drawn from census data: concentrated disadvantage, residential mobility, immigration concentration and racial diversity. Maps show that incidents of VAP tend to cluster spatially, and multivariate analyses suggest that concentrated disadvantage and calls for service, but not other indicators, were significantly related to violence against the police. Future studies of violence against the police should include measures of routine activities theory, as such indicators may be mediating the relationship between community-level factors and VAP. Additionally, future research should attempt multilevel modelling to account for situational factors as well as structural characteristics of the location. Further, theory would significantly move forward if researchers could identify the processes by which structural conditions affect VAP. To decrease injurious assault on police, police administrators may want to refocus community policing efforts. While police are unable to eradicate poverty and other structural social problems, they are in a unique position to work with a variety of local government agencies to alleviate community concerns.